QTL for survival to UV-C radiation in Drosophila melanogaster - Gomez, Federico Hernan (2012)
Purpose: The aim of this study was to investigate tolerance to UV-C (ultraviolet C, 280–100 nm) radiation in Drosophila melanogaster, implementing a quantitative trait locus (QTL) mapping approach. This is of interest to test for genetic variation in survival to UV (ultraviolet) radiation. Materials and methods: We performed a QTL scan in D. melanogaster recombinant inbred lines (RIL) constructed from parental stocks derived from a crossing between northern and southern hemisphere populations that segregated substantial genetic variation in thermal resistance in a previous study. Here, two experimental treatments were implemented: Continuous and cyclic UV-C radiation. Results: Significant QTL were detected on all three major chromosomes. Among these, multiple trait composite interval mapping revealed a significant QTL in the pericentromeric region of chromosome 2, a genome region consistently implicated in thermotolerance in previous studies. Conclusions: This study shows substantial genetic variation for UV-C radiation resistance in D. melanogaster, with QTL for survival to UV-C radiation generally overlapping with major thermotolerance QTL. The genetic architecture of UV-C radiation resistance appears to be more complex in continuously irradiated individuals.